PERGURUAN TINGGI: WAHANA PENGEMBANGAN POTENSI MAHASISWA MENJADI INDIVIDU PRODUKTIF DAN KOMPETEN - Dawud Ardisela (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2005)
Development arrow and strategy in many countries change from the concept of comparative advantage to Competitive advantage that based productifity and added value. Productifity effect to human resources quality and science/technology improvement. Education have important role in human resources quality. Alumni of university especially chemistry academy must be productif, proffesional, efftsien and competen people in global competition.